Prinsip Ibahah Sebagai Solusi Hukum Terhadap Kelemahan Prinsip Wadi'ah Dan Mudarabah Dalam Undang-Undang Perbankan Syari'ah - Hidayah, Khoirul; Suwandi, Suwandi (UIN Sunan Kalijaga, 2014)
ASEAN Free Trade Area (AFTA) and ASEAN Economic Community (AEC) in 2015 have effect to liberalization in good and services in ASEAN area. To face AEC, shari’a banking must support with regulation and law assurance. The writer have argument that some incorrect principles in shari’a banking law. Wadi’ahand mud?rabah principles do not benefit in syari’ah banking. Those principles untruth in Islamic shari’a. There are mass deception in principles using, Islamic shari’a concept are not the same with the practice. Ib?hah principle is the law solution to subtitute the wadi’ahand mud?rabah principles. It is general principle in economic which allowed in any way as long as not contradiction with regulation.